Personal factors influencing the motivation to engage in healthy life behavior: a qualitative study among Indonesian obese adult women - Rusyantia, Anggun; Khomsan, Ali; Kusharto, Clara Meliyanti; Pratomo, Hadi (International Journal Of Community Medicine And Public Health, 2022)
Background: As a part of social cognitive theory (SCT), personal factors can be potential mediators of behavior change. Knowing what motivates adult obese women to carry out healthy life behavior can help program planners develop intervention strategies to overcome obesity. This study examined the personal factors influencing obese women’s motivation to adopt healthy life behaviors. Methods: This descriptive-qualitative study was conducted from July to October 2021 in the city of Bogor, Indonesia. Participants were selected by purposive sampling from eight noncommunicable diseases (NCDs) posts (NCDs Posbindu). The data were collected using semi-structured, open-ended questions using a video conference platform. All the recorded interviews were transcribed verbatim. Thematic analysis with deductive coding (theory-driven) was used to analyse the data. Results: A total of 26 obese women aged 19-40 were interviewed within eight discussion groups. Three theory-driven codes were chosen, and four themes were created from nine clustered codes of the transcripts: “health education and promotion,” “the positive and negative impacts of eating healthy food and exercising regularly on the body and finances,” “facilitators in eating healthy food and exercising regularly,” and “barriers to eating healthy food, exercising and weight monitoring regularly”. Lack of knowledge about weight management guidance, time and resources constraint, and low self-efficacy reduce motivation to continue an activity or target behavior. Conclusions: Obese adult women need more weight-management knowledge, skills, and assistance using the concerned potential mediators. These findings could help program planners design effective health intervention strategies to achieve desired behavior change.